An Online Game and the Effect of Strengthen Vocabulary Knowledge of Efl Students; Indonesian Context - Juang Kurniawan Syahruzah (Departement of Mathematics Education, 2023)
This research aims to identify the effectiveness of using the ONLINE game to teach writing in the EFL classroom in Indonesia. It based on the research problem that the students find difficulties on memorizing English words because they used ineffective strategy.The research used experimental research design. The population in this research was the student of EFL classroom in INDONESIA, then the sample was the 8th grade in the EFL classroom in INDONESIA. The samples were taken by using random sampling technique. This research was conducted in 3 stages: data collection, action and data analysis. The data were collected through test, observation, and questionnaire. The data were analyzed by using the steps of: normality test, homogeneity test, inferential analysis, determining hypothesis testing, and conclusion.The result of this research presents that the onlines game strategy is effective to teach writing at the university level. The hypothesis is determined into the Null hypothesis (H0) and Alternative Hypothesis (Ha). H0 is accepted if the significance value >0.05 and Ha is rejected. The control group’s mean score on the pre-test is 58,11 increases to 59 in post-test with gain point 0,89. The experiment group’s mean score on pre-test was 57,59 increased to 60,89 on post-test with gain point 3,3.